Building the Future of Brain Health: Establishing Neurovascular Services in Southeast Sulawesi - Wibriansyah, Akbar; Adam, Achmad; Zulkifli, Bilzardy Ferry (Riviera Publishing, 2025)
Background: Stroke and other neurovascular diseases are leading causes of death and disability worldwide, particularly in regions with limited healthcare resources. Southeast Sulawesi faces major challenges in providing adequate neurovascular care, including shortages in diagnostic facilities, specialists, and emergency response systems. Addressing these gaps is essential to improving patient outcomes and reducing healthcare disparities. Methods: A mixed-methods approach was employed, combining qualitative data from semi-structured interviews with healthcare providers, policymakers, and patients, with quantitative analysis of official health records and facility observations. The study period spanned from July 2021 to November 2024. Results: In a population of 2.74 million, stroke emerged as the second leading cause of death (17% of total mortality). Infrastructure assessment revealed critical gaps: only 11 of 21 referral hospitals (52.4%, CI 95%: 31.0-73.8%) had CT scanners, with no MRI facilities available. Human resources were severely limited, with only three neurosurgeons (1:914,667 population ratio) and fourteen neurologists (1:196,000). For hemorrhagic stroke cases, surgical intervention showed success rates ranging from 45.8% to 63.6%, with post-operative mortality rates of 15.7-20.8%. The average time to reach CT scan facilities was 4.2 hours (SD ±1.8), significantly exceeding optimal stroke management windows. Geographic and economic barriers further complicated access, with 68% of the population residing more than two hours from neurological care. Conclusions: This study identifies critical gaps in neurovascular service delivery while highlighting potential solutions through systematic infrastructure development, capacity building, and technological integration. The findings suggest that Southeast Sulawesi could develop an effective model for neurovascular care delivery in geographically challenged regions through targeted interventions and strategic resource allocation.